TRANSFORMATIVE TECHNOLOGIES: ARTIFICIAL INTELLIGENCE AND LARGE LANGUAGE MODELS IN QUALITATIVE RESEARCH: AI AND LARGE LANGUAGE MODELS IN QUALITATIVE RESEARCH - Bryda, Grzegorz; Costa, António Pedro (Revista Baiana de Enfermagem‏, 2024)
Objective: To discuss the integration of artificial intelligence and advanced visualization techniques into computerassisted qualitative data analysis software tools. Method: analytical and critical reflection that explores the possibilities, consequences and ethical aspects of this integration. Results: This integration has brought immense benefits and improved coding and analysis processes, the ability of artificial intelligence to deal with large sets of textual data, through innovative methods of visualizing qualitative data. Researchers can interpret and communicate differentiated findings more effectively by transforming data into visual representations with techniques such as diagrams, thematic maps and 2D/3D maps. Conclusion: The incorporation of artificial intelligence, machine learning and natural language processing technologies into computer-assisted qualitative data analysis software tools has automated the identification of themes and relationships in the data, speeding up the research process. Descriptors: CAQDAS. Digital Humanities. Artificial Intelligence. Natural Language Processing. Large Language Models. ChatGPT. Automation.